Leader-Member Exchange, Perceived Organisational Support And Job Satisfaction: Mediating Role Of Employee Engagement - Hazmanan Khair; Jufrizen; Nina Annisa; Ratih Pratiwi; Abdul Rozak (Jurnal Manajemen, 2024)
This study examined the influence of leader-member exchange and perceived organisational support on job satisfaction, with employee engagement as a mediator, either directly or indirectly. This study employs a quantitative associative methodology. This study's participants were all PT Pelabuhan Indonesia (Persero) TPK Perawang employees. This study's sample consisted of a total of 67 employees who were selected using the saturated sampling procedure. Interviews and questionnaires were used for data collection in this study. This investigation employed SEM-PLS for data analysis. This investigation processes data using the Partial Least Square software tool. This study demonstrates that Leader-Member Exchange, Perceived Organisational Support, and Employee Engagement significantly affect Job Satisfaction. Leader-member exchange and Perceived Organisational Support significantly affect Employee Engagement. Leader-member exchange has a significant impact on Job Satisfaction through Employee Engagement, and Perceived Organisational Support has a significant impact on Employee Engagement.